PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAKUL KARIMAH SISWA (Studi Kasus di Sekolah Dasar Negeri Kepatihan 06 Jember) - Farikhin, Fikri; Hamidahtur Rofi'ah, Siti; Maghfirah, Naily Inayatul; Subaidah, Subaidah; Mufarohah, Anis (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Education in Islam does not only aim to produce people who only have intelligence, but also seeks to produce people who have noble character. The phenomenon that occurs in the scope of education assumes that, in the implementation of moral education, the cognitive aspect is still prioritized as a provision of knowledge to students. Where the teacher in front of the class still encourages teaching knowledge, even though it is clear, a teacher's job is not only to transfer knowledge to students but also to instill moral values ​​in shaping students' good character and can be done at school and in the local community. The aim of this research is to describe: The role of Islamic Religious Education Teachers as Guides in Fostering Students' Akhlakul Karimah at Sekolah Dasar Negeri Kepatihan 06 Jember and what are the Supporting and Inhibiting Factors for PAI Teachers in Fostering Students' Akhlakul Karimah at Sekolah Dasar Negeri Kepatihan 06 Jember.